PENGARUH MODAL KERJA, PERPUTARAN PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS MELALUI LIKUIDITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Iqbal, Zainul; Subaida, Ida; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The development of pharmaceutical companies is now growing rapidly and competition is getting tougher, especially for our country Indonesia. Pharmaceutical companies are non-profit businesses that specialize in the development, production and distribution of medicines, especially those related to health. Indonesia's rapidly growing economy is largely driven by pharmaceutical companies. The pharmaceutical industry is currently a rapidly growing industry due to the very high public need for medicines, resulting in an increase in mass consumption, especially multivitamin products and immune enhancers. Based on the current development of the pharmaceutical consumer goods industry, it is not surprising that the number of companies engaged in pharmaceuticals on the Indonesia Stock Exchange has increased greatly. The purpose of this study was to analyze and test the effect of working capital, inventory turnover and sales growth on profitability through liquidity in pharmaceutical companies listed on the IDX in 2020-2023. The population used in this study includes 11 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2023 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing using Structural Equation Analysis - Partial Least Square (PLS-SEM).The results of the research hypothesis test using the Smart PLS 3. 0, shows that working capital has a positive but insignificant effect on liquidity, inventory turnover has a negative but insignificant effect on liquidity, sales growth has a positive but insignificant effect on liquidity, working capital has a positive but insignificant effect on profitability, inventory turnover has a positive but insignificant effect on profitability, Sales growth has a positive but insignificant effect on Profitability, Liquidity has a negative but insignificant effect on Profitability, Working capital has a negative but insignificant effect on Profitability through Liquidity, Inventory turnover has a positive but insignificant effect on Profitability through Liquidity, Sales growth has a negative but insignificant effect on Profitability through Liquidity.